O sentido da caminhada: uma análise sobre os aspectos físicos e sensoriais das calçadas do centro de Uberlândia - Petraglia, Luciana Mendes Carvalho (2015)
This research investigated the quality of sidewalks from the perspective of the user by evaluating the physical aspects and sensory (or perceptive) of the trajectory. The main objective was to understand which attributes are responsible for the quality of the pedestrian trajectory. For this analysis a methodology with multi-methods and valuation techniques was used, which was also divided into two pillars: physical aspects and perceptual aspects. Quantitative methods were used to evaluate physical aspects whereas qualitative methods were employed for perceptual evaluation. The methodology was based on the perspective of the user based on the four perspective planes defined in the Sidewalk Room as roadside plane, canopy plane, ground plane and building wall plane. In order to evaluate the quality of these planes, Post Occupancy Evaluation techniques were applied. Data collection was employed for the physical aspects, whereas interviewing techniques, behavioral map, word cloud and focus group were chosen for the perspective aspect. The data indicate problems related to the physical, acoustic and thermal comfort in the trajectory. Although there is an initial step on the issue of accessibility, its implementation is not suitable. The results suggest that the planes interfere with each other in the trajectory quality. In facades (building wall plane) whose stores are more integrated with the sidewalks (ground plane), directly affecting the flow of pedestrians. The interviews, focal groups and behavioral maps confirm the data of the physical survey, in which the results demonstrate dissatisfaction regarding walk quality. Also a great interest of this research users in the windowshops, shops , the main square in downtown Uberlândia, the Tubal Vilela Square, was manifestated. The results indicate that, despite the heavy flow of people, the quality of the sidewalks from the perspective of the users through its four planes still demands attention by the government.